THE EFFECT OF TEAMWORK, INTERPERSONAL COMMUNICATION AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE IN THE BATAM CITY DISTRICT OFFICE - Putra Khosenda Pratisara Wirya; Sabri; Sumardin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to determine and analyze the influence of Teamwork, Interpersonal Communication, and Leadership Style on Employee Performance at the Batam City District Office. The research method used is a quantitative method with a survey approach. The population in this study were all employees of the Batam City District Office, totaling 75 people. Because the population is less than 100 people, the sampling technique used is a census technique, so that the entire population was used as research respondents. The data collection technique was carried out through the distribution of questionnaires measured using a Likert scale. Data processing and analysis were carried out with the help of the SPSS program through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using t-tests, F-tests, and coefficients of determination (R²).